Effects of meteorological factors on pollen flora in the atmosphere of Sinop (Turkey) - Demır, Cemile Canşı; Özler, Hülya; Kaplan, Ayşe (Bangladesh Journal of Botany, 2021)
This study was conducted for determining the plant taxa of the pollen grain in the atmosphere of the city center of Sinop (Turkey) and investigating the effects of meteorological factors on pollen concentration, by analyzing daily, weekly and monthly changes in the atmosphere. The types and amounts of pollen grain in the atmosphere were determined using Burkard trap. On the basis of the average of 2 years (2016 - 2017), the dominant trees taxa in the atmosphere were Cupressaceae/Taxaceae (32.67%), Pinaceae (15.51%), Morus sp. (5.50%), Quercus sp. (2.76%), Alnus sp. (2.24%), Corylus sp. (1.48%), Carpinus sp. (1.43%), Juglans sp. (1.43%), Fraxinus sp. (1.33%), Olea europaea (1.05%) and Poaceae (Grass) (5.29%), whereas the dominant weed taxa were Urticaceae (11.16%), Ambrosia sp. (4.31%), Amaranthaceae (3.21%), and Mercurialis sp. (2.05%). Temperature and wind speed had a positive effect on the increased amount of pollen, whereas precipitation had a negative effect on it. On the basis of the data obtained, a pollen calendar was prepared for the area.